RESPONSE TO MICROCLIMATE OF MORPHOLOGICAL LEAF ATTRIBUTES, PHOTOSYNTHETIC AND WATER RELATIONS OF EVERGREEN SCLEROPHYLLOUS SHRUB SPECIES - Gratani, L (PHOTOSYNTHETICA, 1993)
Leaf adaptations of Quercus ilex L., Phillyrea latifolia L. and Pistacia lentiscus L. to various environmental conditions namely from the viewpoint of the differences of leaf area, dry mass, chlorophyll (Chl) content, sclerophylly index, succulence index and net photosynthetic rate (P(N)), are shown. Irradiance was the most important factor to influence P(N), leaf temperature, stomatal conductance (g(s) and transpiration rate (E). Under canopy layer low red-far red ratio reduced P(N). Shade leaves were enriched by Chl b. Chl content and sclerophylly index were good leaf characteristics to express adaptability of plants to microclimate.
Keywords: irradiance; leaf area; microclimate; Phillyrea latifolia L.; Pistacia lentiscus L.; Quercus ilex L.